Associations between feeding patterns and clinical outcomes of Hirschsprung’s disease after surgery: propensity score matching approach - Feng, Wei; Xiang, Xiao; Die, Xiaohong; Hou, Jinping; Guo, Zhenhua; Liu, Wei; Hou, Jinfeng; Wang, Yi (Frontiers in Nutrition, 2025)
BackgroundFeeding pattern is closely related to physical development and health, but the benefit of breast feeding on clinical outcomes of Hirschsprung’s disease (HSCR) remains unknown. This study aimed to investigate the influences of feeding patterns on postoperative outcomes of HSCR using propensity score matching (PSM) analysis.MethodsThe clinical data of 296 patients with HSCR who underwent Laparoscopic-assisted pull-through surgery were retrospectively analyzed. Patients were dichotomized into breast and formula feeding groups. Using propensity score matching (PSM), the two groups were compared for baseline differences and postoperative outcomes. Furthermore, Univariate/multivariate Logistic regression analysis was used to identify feeding pattern as an independent factor of postoperative HAEC and bowel dysfunction.ResultsOf the 296 patients, breast feeding was 73% (216/296). After PSM, patients with formula feeding had higher rates of postoperative undernutrition (risk of malnutrition: 21.05% vs. 8.77%; malnutrition: 28.07% vs. 15.79%, p = 0.023), HAEC (47.37% vs. 22.81%, p = 0.006), and bowel dysfunction (64.29% vs. 42.11%, p = 0.018). Multivariate Logistic regression analysis revealed that formula feeding was an independent risk factor for postoperative HAEC [OR (95% CI) = 6.86 (1.76 26.79)] and bowel dysfunction [OR (95% CI) = 2.88 (1.06 7.83)].ConclusionFollowing adjustment for patient characteristics, HSCR patients with breast feeding were associated with lower rates of postoperative undernutrition, HAEC, and bowel dysfunction.